2015
DOI: 10.1063/1.4935221
|View full text |Cite
|
Sign up to set email alerts
|

Development of a compact ECR ion source for various ion production

Abstract: There is a desire that a carbon-ion radiotherapy facility will produce various ion species for fundamental research. Although the present Kei2-type ion sources are dedicated for the carbon-ion production, a future ion source is expected that could provide: (1) carbon-ion production for medical use, (2) various ions with a charge-to-mass ratio of 1/3 for the existing Linac injector, and (3) low cost for modification. A prototype compact electron cyclotron resonance (ECR) ion source, named Kei3, based on the Kei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The success of the CUBE-ECRIS and the prospects of the ARC-ECRIS will inevitably be defined through a comparison to existing PM ECR ion sources. The reported beam currents of different sources are listed in table 6 in the supplementary material [38][39][40][41][42][43][44][45][46]. An especially interesting case is the BIE100 PM ECRIS [41] performing extremely well (reaching charge states such as Ar 17+ ) at 12.75 and 14 GHz for both of which it has lower mirror ratios (B max /B ECR ) in all directions along the escaping flux and weaker extraction field than the CUBE-ECRIS.…”
Section: Discussionmentioning
confidence: 99%
“…The success of the CUBE-ECRIS and the prospects of the ARC-ECRIS will inevitably be defined through a comparison to existing PM ECR ion sources. The reported beam currents of different sources are listed in table 6 in the supplementary material [38][39][40][41][42][43][44][45][46]. An especially interesting case is the BIE100 PM ECRIS [41] performing extremely well (reaching charge states such as Ar 17+ ) at 12.75 and 14 GHz for both of which it has lower mirror ratios (B max /B ECR ) in all directions along the escaping flux and weaker extraction field than the CUBE-ECRIS.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the Gunma University Heavy Ion Medical Center (GHMC [3]) started operating as a carbon-dedicated demonstration facility. A compact ECR ion source for GHMC, the KeiGM, is also based on the development of compact ECR ion sources (Kei series) at NIRS [4]. Kei series were installed at the GHMC, the Saga Heavy Ion Medical Accelerator in Tosu, the Ion-beam Radiation Oncology Center in Kanagawa, the Osaka Heavy Ion Therapy Center and the East Japan Heavy Ion Center in the Yamagata University.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, our group has been conducting to increase the yield of multicharged ions by introducing other electromagnetic waves without changing the magnetic field strength and microwave frequency. We focus on the gas mixing effect [2] [3], which is known as an empirical method to increase multicharged ions in ECRIS's. In our previous studies, the increase of Ar multicharged ion yield has been confirmed by the upper hybrid resonance (UHR) [4] using 4-6 GHz Xmode microwaves, the dual ECR heating method [5] in which microwaves are fed from two antennas simultaneously.…”
Section: Introductionmentioning
confidence: 99%